Begonia medicinalis (Begoniaceae), a new species from Sulawesi, Indonesia - Ardi, Wisnu H.; Zubair, Muhammad S.; -, Ramadanil; Thomas, Daniel C. (Phytotaxa, 2019)
A new species of Begonia, Begonia medicinalis Ardi & D.C.Thomas, is described from Sulawesi, Indonesia. A photo plate and distribution map are provided. The new species is endemic to Sulawesi and belongs to Begonia section Petermannia.